FORM AND MEANING OF TI'I KA DISCOURSE IN MBASA WINI RITUAL OF RONGGA ETHNIC IN FLORES - Sumitri, Ni Wayan; Weda Kusuma, I Nyoman; Suarka, I Nyoman; Bustan, Fransiscus (e-Journal of Linguistics; Vol. 9 Januari 2015 No. 1)
This article describes the results of research on the form and meaning of Ti'i ka discourse (TD) that is the food offering ritual to the ancestors in mbasa wini rituals in Rongga ethnic of Flores. Mbasa wini ritual is the new-year ritual of traditional agricultural in Rongga ethnic. Theoretical framework to guide is cultural linguistic supported by discourse, symbolic interactions and hermeneutics theories. This research is a descriptive study based on the philosophy of phenomenology. The location of the study is in the distribution of Rongga ethnic region with the main location in the Sambi Village sub-District of Kota Komba, East Manggarai regency. Methods of data collection are observation, interviews, and documentary studies. The data collection technique is recording and note-taking. The main data sources are Rongga ethnic residing in Sambi village that were represented by four key informants. The data were analyzed qualitatively using induction method. The results showed that the form and meaning of TD is unique in the context of the situation of mbasa wini ritual and socio-cultural context of Rongga ethnic. The specificity of the form is characterized by the use of complex sentences as meaning container that exposed Rongga ethnic conceptualization of the world. Type meanings include religious meaning, social, economic, and aesthetic. Religious significance related to the conceptualization of the existence of God, the spirit of ancestors, and nature spirits. The social significance is marked by the presence of people gathered as rituals participants and communication between them by using language of Rongga as a medium. Economic significance with regard to the economic system that was involved by Rongga ethnic is agricultural and farming systems. Political meaning is marked by power differences between ritual leaders and rites participants. Aesthetical meaning is reflected in the use of phonological parallelism in the form of assonance, rhyme, and alliteration. It is recommended that the Government of East Manggarai district document TDMW in printed and electronic, as well as the Rongga ethnic to make the mechanism of inheritance through mbasa wini rituals regularly and intensively every year.
Keywords: forms, meanings, Ti' ika discourse, mbasa wini ritual, Rongga ethnic